Oh cryoprotectant, wherefore art thou cryoprotectant? Investigation of the permeation of common cryoprotectants into live rice callus cells by coherent Raman microscopy - Samuels, Fionna M. D., author; Levinger, Nancy E., advisor; Van Orden, Alan, committee member; Crans, Debbie C., committee member; Wilson, Jesse W., committee member (Colorado State University. Libraries, 2023)
Conserving a diverse selection of plant species is vital as climate change begins shifting the planet's ecosystems in earnest. Many plants can be preserved through maintaining their seeds in cool, dark chambers, like that of the Svalbard Seed Vault, but others do not reliably reproduce through seeds. This can include wild plants that lack seeds entirely, ferns for example, or agricultural plants where clonal propagation is the only way to conserve desirable traits, grapes, hops and bananas for example. Rather than collecting and saving seeds from these plants, researchers collect tissue samples, cool and preserve them in liquid nitrogen then warm and regrow the plants years later. To maximize post-freezing viability, tissue samples are exposed to mixtures of cryoprotectants. Only a few cryoprotectant formulations have been used almost exclusively since their development in the early 1990s, including Plant Vitrification Solution 2 (PVS2) and Plant Vitrification Solution 3 (PVS3). Unfortunately, these formulations are not universally protective—some plant species respond extremely well to exposure while others are killed. When PVS2 or PVS3 fail to preserve a species, researchers must either empirically develop a new formulation or method of cryopreservation or settle for not conserving the species. A lack of mechanistic understanding of how these formulations work to protect tissue from extreme cold prevents straightforward development of new formulations. Since the development of PVS2 and PVS3, advances in instrumental techniques have opened the door to improved physical characterizations of the components of these mixtures. Vibrational microscopies, like Raman or infrared microscopy, allow the direct visualization of cryoprotectants interacting with living cells. By exciting vibrations unique to the bonds in a molecule, these techniques can effectively image nearly unadulterated molecules. Through deuteration, cryoprotectants can be imaged without disturbing other molecules in the cell. The work presented in this dissertation demonstrates how deuterated dimethyl sulfoxide (d6-DMSO), deuterated ethylene glycol (d6-ethylene glycol) and deuterated glycerol (d8-glcyerol) can be directly imaged inside living rice callus cells. Readers are first introduced to the cell system, rice callus cells, and the analytical technique, coherent anti-Stokes Raman scattering (CARS) microscopy. Then, they will learn about initial static experiments searching for the location of d6-DMSO within the callus cells. The next two chapters explore the real-time permeation of d6-DMSO, d6-ethylene glycol and d8-glcyerol individually and then solvated in PVS2. The final chapter describes future experiments I think should come from this work that will increase fundamental understanding of cryoprotectant-cell interactions and streamline the process of developing new cryoprotectant formulations.
Zip file contains supplementary videos, no sound.
Keywords: permeation; Raman microscopy; cryoprotectant; rice callus cells; plant cryopreservation